Energy and presence: A journey from theatre lab to teacher training - Isabelle Gatt (SCENARIO: Journal for Performative Teaching, Learning, Research)
This article narrates my journey through laboratory physical theatre, focusing on how actor presence emerges from physical training, imagination, intentionality and connection with the audience. It then argues for the significance of these elements in initial teacher training, exploring the concept of teacher presence and examining to create a more embodied and active engagement in the classroom, similar to the craft of an actor in performance. By integrating actor-training, I propose that presence is something developed through laboratory theatre training techniques. In my work with student teachers, I incorporate such techniques to work on their energetic presence, enabling them to create richer emotional connections with their students. Research indicates that strong teacher-student relationships significantly impact academic achievement, motivation, and engagement. These relationships flourish when teachers leverage their mental, physical, and emotional resources, suggesting that presence is not merely an innate quality but a skill that can be developed through specific actor-training exercises. Student logs of reflections on the drama module sessions will illustrate the transformative impact of this training on their confidence, teaching practices, and the relationships cultivated within the classroom. Ultimately, I posit that when educators engage their intellect, emotions, and creativity, they can create dynamic learning environments that resonate with authenticity and connection.